Science seminar: Who has the right to climate change adaptation? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
On 18 February 2013, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) organised, together with the Danish Institute for International Studies (DIIS) and the University of Copenhagen, a live-streamed science seminar entitled: "Who has the right to climate change adaptation". The seminar explored the social dimensions of climate change: how development programming needs to embrace resilience, the transformative cornerstones of social science research for climate change, and gender and social differentiation in building agricultural climate resilience. View CCAFS live-streamed seminars here: http://www.ccafs.cgiar.org/videostream